1967
DOI: 10.1111/j.1570-7458.1967.tb02468.x
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between the Size of Yellow Water Traps and Catches of Aphids

Abstract: Yellow water traps are often used for sampling populations of flying aphids. This note suggests that the size and probably the shape of traps should be standardised, because trapping efficiency (nos. caught/unit area), and the relative attractiveness of traps to different species, depends on trap size. Aphidologists using water traps to compare mixed populations of flying aphids, should therefore compare catches from different traps with caution. Traps of three sizes were made up from individual trays, each 29… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1980
1980
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…containers, small ground pools), might wet mosquitoes that rest on the water surface to oviposit. The relationship between numbers caught and trap areas was linear on a V X V scale for aphids, with trapping efficiency per unit area decreasing with larger traps (Costa & Lewis, 1968). It was concluded that at least some of the aphids were visually attracted to the traps.…”
Section: Different Types Of Sticky Trapsmentioning
confidence: 92%
“…containers, small ground pools), might wet mosquitoes that rest on the water surface to oviposit. The relationship between numbers caught and trap areas was linear on a V X V scale for aphids, with trapping efficiency per unit area decreasing with larger traps (Costa & Lewis, 1968). It was concluded that at least some of the aphids were visually attracted to the traps.…”
Section: Different Types Of Sticky Trapsmentioning
confidence: 92%
“…Nonsignificant interactions were pooled with residuals. The numbers of aphids caught in the water traps were divided by 2.84 to compensate for the larger surface area of the water trap compared with the STP traps and the numbers in the water trap were multiplied by 1.05 to account for the effect of larger size on efficiency (Costa and Lewis 1967). Data are expressed as either number per day per trap or number per day per square centimetre.…”
Section: Methodsmentioning
confidence: 99%
“…Trap size itself may affect catch size. Costa & Lewis (1967), using aphid catches in yellow water traps, showed that an approximately 8-fold increase of trap area was associated with an approximate halving of number of aphids per 100 cm2, and species were attracted to traps of different areas differentially.…”
Section: (I) Estimate Of Rate Of Fall-outmentioning
confidence: 99%